Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Le contrôle de notre corps est politique - Coordination nationale pour l'avortement libre et gratuit; Gaucher, Dominique (La pensée féministe au Québec: Anthologie 1900-1985, 2003)
Première publication: 1979 https://search.ebscohost.com/login.aspx?direct=true&db=nlebk&AN=2747752&lang=fr&site=ehost-live
Keywords: 1900-1999; amériques; avortement; corps; cours; droits des femmes*; fem1000; justice reproductive; militance; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé reproductive; thématiques; violences

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Travailler à l'élimination du trafic sexuel des femmes - Matte, Diane; Kurtzman, Lyne (Canadian Woman Studies, 2003)
Au cours des deux dernieres annees, le mouvement des femmes du Quebec a ete happe par le debat concernant la prostitution et le trafic sexuel. Dans le contexte de l'organisation de la Marche mondiale des femmes, un groupe de Montreal, Stella, regroupant des travailleuses du sexe et qui est membre de la Federation des femmes du Quebec (FFQ) a propose que la Marche quebecoise porte des revendications concernant la decriminalisation de l'industrie du sexe en se basant sur une analyse: qui reconnait la prostitution comme un metier comme un autre; qu'il est utopique de vouloir l'eliminer; que cette lutte serait contre-productive au regard des besoins des femmes prostituees et que la priorite du mouvement des femmes doit etre de mettre fin a la discrimination envers les femmes dans cette industrie. Le debat etait lance et n'a pu etre resolu autour des revendications quebecoises de la Marche mondiale des femmes. Les femmes du Quebec ont tout de meme defendu des revendications reconnaissantl'importance de mettre fin a la discrimination dont sont victimes les prostituees dans le systeme judiciaire et les services sociaux et denoncant la violence et les abus dont elles sont victimes. Par rapport a ces grandes lignes, on peut affirmer qu'il y a consensus.
Keywords: amériques; approches et analyses; canada; communication; corps; cours; discipline; justice sociale; premier cycle; prostitution; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; travail; violences

D'Eros, des poissons et des femme - Pelletier, Francine (La pensée féministe au Québec. Anthologie (1900-1985), 2003)
Première publication 1980
Keywords: 1900-1999; amériques; corps; cours; fem1000; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sexualité; thématiques